1999
DOI: 10.1101/lm.6.6.619
|View full text |Cite
|
Sign up to set email alerts
|

A Nitric Oxide-Independent and β-Adrenergic Receptor-Sensitive Form of Metaplasticity Limits θ-Frequency Stimulation-Induced LTP in the Hippocampal CA1 Region

Abstract: The induction of long-term potentiation (LTP) and long-term depression (LTD) at excitatory synapses in the hippocampus can be strongly modulated by patterns of synaptic stimulation that otherwise have no direct effect on synaptic strength. Likewise, patterns of synaptic stimulation that induce LTP or LTD not only modify synaptic strength but can also induce lasting changes that regulate how synapses will respond to subsequent trains of stimulation. Collectively known as metaplasticity, these activity-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…Neuromodulatory transmitters play critical roles in regulating activity-dependent synaptic plasticity (Moody et al, 1999;Mann and Greenfield, 2003;van Dam et al, 2004). Neuromodulators such as noradrenaline can alter the sensitivity of LTP to electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromodulatory transmitters play critical roles in regulating activity-dependent synaptic plasticity (Moody et al, 1999;Mann and Greenfield, 2003;van Dam et al, 2004). Neuromodulators such as noradrenaline can alter the sensitivity of LTP to electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, NMDAR-based metaplasticity, which can be either inhibitory or potentiating, at excitatory synapses has been most systemically examined. The inhibitory role of NMDAR-based metaplasticity was first demonstrated in the hippocampus, where it has been shown that low-level activity of NMDARs increases the induction threshold of subsequent LTP (Izumi et al, 1992; Larkman et al, 1992; Christie et al, 1995; Moody et al, 1999). This form of inhibitory metaplasticity seems to be mediated either by activation of the high affinity Ca 2+ -signaling, upregulation of the converging inhibitory synaptic input, or desensitization of LTP-associated molecular machineries (Davies et al, 1991; Komatsu, 1994; Chard et al, 1995; Malenka and Nicoll, 1999).…”
Section: Silent Synapses As Metaplasticity Substrates In the Nacmentioning
confidence: 99%
“…Activity-dependent synaptic plasticity is a critical mechanism for learning and memory, and neuromodulatory transmitters play a vital role in regulating synaptic strength (Moody et al 1999;Mann and Greenfield 2003;van Dam et al 2004). Previous studies have found that when b-ARs are activated by ISO, maintenance of LTP is prolonged following a single train of HFS that, alone, is insufficient to elicit long-lasting potentiation (Gelinas and Nguyen 2005; see also Dahl and Li 1994 for dentate gyrus data).…”
Section: Discussionmentioning
confidence: 99%